Repeatability and reproducibility of corneal biometric measurements using the visante omni and a rabbit experimental model of post-surgical corneal ectasia - Liu, Yu-Chi (2020)
Purpose: To investigate the repeatability and reproducibility of the Visante Omni topography in obtaining topography measurements of rabbit corneas and to develop a post-surgical model of corneal ectasia. Methods: Eight rabbits were used to study the repeatability and reproducibility by assessing the intra- and interobserver bias and limits of agreement. Another nine rabbits underwent different diopters (D) of laser in situ keratosmileusis (LASIK) were used for the development of ectasia model. All eyes were examined with the Visante Omni, and corneal ultrastructure were evaluated with transmission electron microscopy (TEM). Results: There was no significant intra- or interobserver difference for mean steep and flat keratometry (K) values of simulated K, anterior, and posterior elevation measurements. Eyes underwent -5 D LASIK had a significant increase in mean amplitude of astigmatism and posterior surface elevation with time (P for trend < 0.05). At 2 and 3 months, the -5 D LASIK group had significant greater mean amplitude of astigmatism (P = 0.036; P = 0.027) and posterior surface elevation (both P < 0.005) compared with control group. On TEM, the mean collagen fibril diameter and interfibril distance in the -5 D LASIK eyes were significantly greater than in controls at 3 months (P = 0.018; P < 0.001). Conclusions: The Visante Omni provided imaging of the rabbit cornea with good repeatability and reproducibility. Application of -5 D LASIK treatment produced a rabbit model of corneal ectasia that was gradual in development and simulated the human condition. Translational Relevance: The results provide the foundations for the future evaluation of novel treatment modalities for post-surgical ectasia and keratoconus.